THE ANALYSIS OF ENGLISH LOAN AND BORROWING WORDS USED BY INFORMATION AND TECHNOLOGY WRITERS IN THESIS ABSTRACTS - luh mas ariyati (JURNAL SOSIAL HUMANIORA (JSH), 2014)
An analysis on a field of linguistics that is English loan words can cause problems, such as problems of spelling and pronunciation, or even the change in meaning of the English borrowed words. This research is expected to give contribution to the society in general should be aware of the practical use of English loan words in Indonesian. In particular, the IT people can spell and write all the English borrowed words correctly in their writing in accordance with the rules of EYD, especially in formal writing. For EFL teachers and students, this study is aimed to explain practical inputs in teaching ESP writing, loan words, and the development of loan words in relation to linguistics, particularly loan words, such as definitions of loan words, patterns of borrowing and reasons for borrowing. Furthermore, the Indonesian lexicologist, can use the findings of the study to develop the glosarium into comprehensive IT dictionary deriving from English words including how to spell and pronounce them correctly.